Enjambment and its realisation(s) in speech - Grošelj, Nada (Acta neophilologica, 2002)
With regard to the question how enjambment should be rendered in the recitation of poetry, three conflicting approaches may be identified: continuing into the next line without marking the line-ending at all; making a break in the intonation and rhythm at the line-ending; and finally, acknowledging the line-ending by merely introducing a short pause without any intonation changes. Each of this renditions has different consequences for the listener's perception of the text. This paper reviews the three approaches and their implications, concluding that the most imprtant criterion for the preference of one approach over another is the type of verse (free vs. metrical) in a given text.
Keywords: recitiranje; retorika; rhetoric; verzologija